Barriers and facilitators of medication adherence in the management of diabetes among the Brazilian Amazon population - Andrade, Raquel Coelho de; Ueno, Thalyta Mariany Rego Lopes; Farias, Tiago Assunção dos Santos; Monteiro, Wagner Ferreira; Campos, Hércules Lázaro Morais; De Leon, Elisa Brosina (Revista Cuidarte, 2026)
Highlights• This study examines the challenges to medication adherence among individuals with type 2 diabetes living in remote Amazonian areas.• Environmental, social, and systemic factors significantly influence patients' ability to sustain consistent use of prescribed antidiabetic medications.• Community health workers play a crucial role in bridging gaps in Diabetes care within hard-to-reach Amazonian communities.• The findings underscore the need for culturally adapted, territory-based strategies to improve medication adherence and chronic disease management.Introduction: Type 2 diabetes mellitus (T2DM) is a prevalent chronic condition with global impact. Medication adherence is essential for disease control, but it remains a challenge in socially vulnerable contexts such as the Brazilian Amazon. Objective: To identify barriers and facilitators of medication adherence in the management of T2DM in the Amazon population. Materials and Methods: A qualitative, descriptive study was conducted in Iranduba (Amazonas) involving individuals with T2DM and community health workers (CHWs). The World Café method and semi-structured interviews were used. Data were analyzed with the support of ATLAS.ti software, using Thematic Network Analysis. Results: A total of 64 participants were included (47 individuals with T2DM and 17 CHWs). Reported barriers included difficulty remembering medication schedules, adverse effects, limited financial resources, lack of medication availability in primary care, and insufficient professional support. Facilitators included self-management strategies, commitment to treatment, purchasing power, family support, and CHWs' actions. Discussion:  Medication adherence in diabetes is shaped by barriers such as forgetfulness, adverse effects, and limited access to medications, while family support, professional guidance, and personal strategies facilitate treatment. These factors interact and affect self-care.  Conclusion: Medication adherence among individuals with T2DM in the Amazon is shaped by intrapersonal, interpersonal, and environmental factors. Culturally adapted strategies, greater professional support, and public policies ensuring medication availability are essential to improving care and preventing complications.How to cite this article: Andrade, Raquel Coelho de; Ueno, Thalyta Mariany Rêgo Lopes; Farias, Tiago Assunção dos Santos; Monteiro, Wagner Ferreira; Campos, Hércules Lázaro Morais; De Leon, Elisa Brosina. Barriers and facilitators of medication adherence in the management of Diabetes among the Brazilian Amazon population. Revista Cuidarte. 2026;17(1):e5207.  https://doi.org/10.15649/cuidarte.5207
Keywords: Healthy Lifestyle; Vulnerable Population; Noncommunicable Diseases; Primary Health Care; Healthcare Disparities